Field Acceptability of Improved Cotton Picking Bag on Drudgery Reduction of Farm Women - Kanta Sabharwa , Urmila Devi and R.D. Panwar, (Indian Journal of Extension Education, 2016)
The present study was conducted in two villages viz., Dhanda Kheri and Dumerkhan of Jind District of Haryana state onpurposively selected sample of 30 rural women respondents, who were actively involved in cotton picking. Therespondents were demonstrated three types of cotton picking bags (cot-bag) viz traditional cloth and modified cot-bag.These two types of cot-bags were given to respondents for cotton picking and their responses towards each type of cot-bagwere comparatively assessed on different parameters viz perceived health hazards or pain during cotton picking, impact ofbiomechanical, grip and physical stresses and tool factors and field acceptability. Each attribute was assessed with opinionof respondents as strongly agreed (S.A.), agreed (A) and disagreed (D). The data were collected by personallyinterviewing the respondents through a well structured interview schedule and were statistically analyzed.